Implementation Of Marketing Mix Strategies In Laundry Businesses During Social Distancing Policies; Case Study At Sangun Laundry, Serpong, South Tangerang, Indonesia - Abdul Haris; Juhaeri; Novitasari, Sela (International Journal of Scientific Research and Management (IJSRM), 2023)
This research aims to find out and analyze how to correct weaknesses and utilize the strengths of the laundry business during the current Covid 19 pandemic, in addition to knowing and analyzing the best marketing strategies through the analysis of the most appropriate marketing mix strategy in the current COVID-19 pandemic.  The method used in this study uses a qualitative approach based on a case study.  In this study, it was found that the implementation of an effective marketing mix strategy during the COVID-19 pandemic was to focus on a combination of strength and opportunity strategies or SO, including determining the differentiation of marketing strategies. The strategies applied are product innovation strategies, dynamic pricing strategies, network expansion strategies, promotion expansion strategies, human resource effectiveness strategies, excellent service strategies, and premium packaging strategies.